A five-minute drainage assessment prevents reexploration for bleedingCentral MessagePerspective - Go Yamashita, MD; Shingo Hirao, MD, PhD; Atsushi Sugaya, MD; Jiro Sakai, MD; Tatsuhiko Komiya, MD, PhD (JTCVS Open)
Objective: To evaluate the effectiveness of the five-minute drainage assessment (FMDA) in preventing reexploration for bleeding following cardiovascular surgery. Methods: This retrospective review included 1280 patients who underwent cardiovascular surgery between January 2017 and August 2021. Patients were divided into control (n = 695) and FMDA (n = 585) groups. The FMDA involved estimating the bleeding volume from 1 drainage tube every 5 minutes during sternal closure. Reexploration rates, postoperative bleeding volumes, and clinical outcomes were compared between the 2 groups. Results: The FMDA group had a significantly lower rate of reexploration for bleeding than the control group (2.2% vs 4.3%; P = .038). The median postoperative bleeding volume within 24 hours was significantly lower in the FMDA group compared to controls (630 mL vs 695 mL; P = .009). Multivariable logistic regression analysis demonstrated that the FMDA was independently associated with a reduced risk of reexploration for bleeding (odds ratio, 0.49; 95% confidence interval, 0.25-0.96; P = .037). The FMDA demonstrated good discriminatory ability for identifying patients at risk of reexploration (area under the receiver operating characteristic curve = 0.782), with an optimal cutoff of 21.0 mL. Conclusions: Implementation of the FMDA was associated with a significantly lower rate of reexploration for bleeding compared to the control group. The FMDA provides a simple and reproducible approach that can be readily adopted in surgical practice.